Mediterranean diets supplemented with virgin olive oil and nuts enhance plasmatic antioxidant capabilities and decrease xanthine oxidase activity in people with metabolic syndrome: The PREDIMED study. Issue 12 (27th October 2016) - Sureda, Antoni; Bibiloni, Maria del Mar; Martorell, Miquel; Buil‐Cosiales, Pilar; Marti, Amelia; Pons, Antoni; Tur, Josep A.; Martinez‐Gonzalez, Miguel Ángel; ,
Abstract : Adherence to the Mediterranean diet has been associated with a reduction in cardiovascular mortality. Oxidative stress is involved in the origin of this and other metabolic illnesses. This study (part of PREDIMED study) shows that five years intervention with Mediterranean diet enriched with virgin olive oil or nuts enhances antioxidant and decreases oxidative activity in metabolic syndrome patients. Abstract : Scope: This study assessed plasmatic antioxidant capabilities and xanthine oxidase (XOX) activity in metabolic syndrome patients after 5 years intervention with Mediterranean diet (MeDiet) supplemented with extra‐virgin olive oil or with nuts or with low‐fat diet (the PREDIMED [PREvención con Dieta MEDiterránea] study). Methods and results: Seventy‐five participants were randomly selected. Daily energy and nutrient intake were assessed with a validated 137‐item food frequency questionnaire, and adherence to the MeDiet was assessed using a 14‐item questionnaire. Catalase, superoxide dismutase (SOD), myeloperoxidase, XOX activities and protein levels, and protein carbonyl derivatives, nitrotyrosine, nitrite and nitrate levels were determined in overnight fasting venous blood samples. The plasma activity and protein levels of SOD and catalase were significantly higher and XOX activity was lower in MeDiet supplemented with extra‐virgin olive oil and MeDiet supplemented with nuts than in the control group. Participants in both MeDiet groups showed higher plasma nitrate levels than in the control group. Adherence to the MeDiet showed a positive correlation with SOD and catalase plasma antioxidant activities. Conclusion: A MeDiet enriched with either virgin olive oil or nuts enhances the plasma antioxidant capabilities and decreases XOX activity in patients with the metabolic syndrome but we did not observe changes in myeloperoxidase or markers of oxidative damage.